2017
DOI: 10.1002/cphc.201601327
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Structural Stability of Amyloid Motif Fibrils Mediated by Water Molecules

Abstract: In biological systems, structural confinements of amyloid fibrils can be mediated by the role of water molecules. However, the underlying effect of the dynamic behavior of water molecules on structural stabilities of amyloid fibrils is still unclear. By performing molecular dynamics simulations, we investigate the dynamic features and the effect of interior water molecules on conformations and mechanical characteristics of various amyloid fibrils. We find that a specific mechanism induced by the dynamic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
1
3
0
Order By: Relevance
“…Second, the smaller the entropy cost required to elongate the length, the faster the length can be increased, and third, convergence value of the necessary entropy cost is related to the convergence of growth rate. Besides, these entropy cost roles could be supported by previous studies on entropy exchange between hydroshells and amyloids that elucidated amyloid growth mechanisms ,. Our results can help in understanding why membranes promote amyloid aggregations in terms of entropy cost.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Second, the smaller the entropy cost required to elongate the length, the faster the length can be increased, and third, convergence value of the necessary entropy cost is related to the convergence of growth rate. Besides, these entropy cost roles could be supported by previous studies on entropy exchange between hydroshells and amyloids that elucidated amyloid growth mechanisms ,. Our results can help in understanding why membranes promote amyloid aggregations in terms of entropy cost.…”
Section: Resultssupporting
confidence: 79%
“…Characterizing the oligomers that p3 peptides form is important in identifying the toxic mechanisms associated with AD diseases. A number of theoretical MD studies revealed conformational characteristics of p3 fibrillar oligomers and protofibrils, including the effect of hydrophobic residues and salt‐bridges on structural stability and mechanical properties, formation of Aβ‐Tau mixtures, the role of fibrillar oligomers as water channels, and predicted amyloid pore conformation ,,. These results provided insights into Aβ fibrillar oligomer structural characteristics and functional roles.…”
Section: Resultsmentioning
confidence: 92%
“…Deformation of the protein structure occurs where the degrees of freedom of the structure are high. As shown in previous studies, deformation of Aβ oligomers occurs when the existing partial hydrogen bonds are broken, or new hydrogen bonds are formed, inducing local motion of the partial regions. ,,, Such deformation has been related to the vibration mode shape of the protein structure. , The proto-fibrillar morphology was observed in case I; the bent morphology was observed in cases II, III, and IV; and the overtwisted morphology was observed in case V (Figure A).…”
Section: Results and Discussionmentioning
confidence: 60%
“…could affect the stability of Aβ oligomers in the fibrillization process. Most of the structural characteristics of Aβ showed a relation with fibrillization. However, irregular conformations, that do not seem to be associated with fibrillization, were often observed in the case of long Aβ oligomers. ,, Especially, as we have revealed in our previous studies, the over 20-mer Aβ oligomer exhibited an excessively bent conformation that could be clearly distinguished from Aβ proto-fibrils. Single oligomer MD simulations may be regarded as a low oligomer concentration environment, because the single oligomer cannot aggregate with other oligomers. Therefore, we conjecture that this bent oligomer might be associated with the manifestation of different morphologies (i.e., annular or spherical oligomers) at low Aβ concentration.…”
Section: Results and Discussionmentioning
confidence: 84%